Facile synthesis of ZnNC derived from a ZIF-8 metal-organic framework by the microwave-assisted solvothermal technique as an anode material for lithium-ion batteries. (25th April 2022) - Moustafa, M. G.; Aboraia, Abdelaziz M.; Butova, Vera V.; Elmasry, F.; Guda, Alexander A.
Abstract : A zeolitic imidazolate framework-8 (ZIF-8) electrode is a good candidate as an anode material. Abstract : A zeolitic imidazolate framework-8 (ZIF-8) electrode is a good candidate as an anode material. However, further developments of ZIF-8 electrodes present a major challenge owing to their excessively time-consuming preparation processes. To overcome this issue, here, we prepared a ZIF-8 material within 15 min by the microwave-assisted solvothermal technique. The structural properties of the samples before and after annealing were examined by XRD, whereas the local atomic and electronic structures were studied by X-ray absorption spectroscopy (XAS). XRD data exhibited the formation of the ZIF-8 material. XRD data also affirmed the formation of an amorphous phase ZnNC after annealing under N2 . XAS results revealed that the ZIF-8 material converted to ZnNC after annealing under N2 . Moreover, the morphology was investigated by HRTEM with elemental analysis. The surface areas of ZIF-8 and ZnNC samples were studied and found to be 1610 cm 2 g −1 and 276 cm 2 g −1, respectively. The ZnNC material revealed higher discharge and charge capacities of ∼826 and 447 mA h g −1, respectively. The coulombic efficiency of the ZnNC electrode considerably improved from 52% in the 1 st cycle to 95% in the 4 th cycle, signifying a good stability over the subsequent cycles. The satisfactory structural and electrochemical characteristics of the ZnNC electrode make this electrode a promising anode material for lithium-ion batteries.